Light-emitting device and display device

By using two hole transport materials mixed with core-shell structure quantum dots in quantum dot light emitting devices, the problem of insufficient luminescence efficiency and lifetime is solved, and the effect of efficient composite luminescence and long lifetime is achieved.

CN119183311APending Publication Date: 2024-12-24TCL TECHNOLOGY GROUP CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310750696.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The luminous efficiency and service life of existing quantum dot light emitting devices are insufficient, making it difficult to meet industrial needs.

Method used

A hole transport layer with a mix of two hole transport materials is used to match the quantum dots of the core-shell structure to ensure high hole injection efficiency, reduce the probability of charging of the device, and improve luminous efficiency and lifetime.

Benefits of technology

It significantly improves the luminous efficiency and service life. By accurately controlling the energy level and mobility of the hole transport layer, it enhances the hole injection level, ensures efficient composite luminescence, and extends the service life of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119183311A_ABST
    Figure CN119183311A_ABST
Patent Text Reader

Abstract

The invention discloses a light-emitting device and a display device.The light-emitting device comprises an anode, a hole transport layer, a light-emitting layer and a cathode which are sequentially arranged in a stacked mode, the absolute value of the energy level difference between the hole transport layer and the light-emitting layer is 0.1 eV to 1.6 eV, the hole transport layer comprises a first hole transport material and a second hole transport material, and the first hole transport material and the second hole transport material are sequentially stacked. The mobility of the first hole transport material is 2 * 10 <-6 >-1 * 10 <-3 > cm < 2 > / Vs, and the mobility of the second hole transport material is greater than or equal to 1 * 10 <-3 > cm < 2 > / Vs; the material of the light-emitting layer comprises core-shell quantum dots, the core-shell quantum dots comprise a first shell layer and a second shell layer from inside to outside, the material of the first shell layer is ZnSe, and the material of the second shell layer is CdZnS. The invention aims to improve the luminous efficiency and the service life of the light-emitting device at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of display, and in particular to a light-emitting device and a display apparatus. Background Art

[0002] Light-emitting devices emit light by releasing energy through the recombination of electrons and holes, and are widely used in the field of lighting. In recent years, quantum dots (QDs) have attracted widespread attention from industry, academia, and research circles due to their advantages of high fluorescence quantum yield, good monochromaticity, continuously adjustable emission spectrum with size, and strong photochemical and thermal stability. Quantum dot light emitting diodes (QLEDs) constructed with quantum dots as the light-emitting layer have become one of the most active scientific research topics due to their many advantages such as low cost, high brightness, wide color gamut, and excellent solution processability, and have shown great competitive potential in the next generation of flat panel display and solid-state lighting applications.

[0003] Among QLED devices, high-efficiency and long-life devices are the basis for promoting the industrialization of QLED products. Summary of the invention

[0004] In view of this, the present application provides a light-emitting device and a display device, aiming to simultaneously improve the light-emitting efficiency and service life of the light-emitting device.

[0005] The embodiment of the present application is implemented as follows:

[0006] In a first aspect, the present application provides a light-emitting device, comprising an anode, a hole transport layer, a light-emitting layer, and a cathode stacked in sequence, wherein the absolute value of the energy level difference between the hole transport layer and the light-emitting layer is 0.1 to 1.6 eV, and the hole transport layer comprises a first hole transport material and a second hole transport material, and the mobility of the first hole transport material is 2×10 -6 ~1×10 -3 cm 2 / Vs, the mobility of the second hole transport material is greater than or equal to 1×10 -3 cm 2 / Vs;

[0007] The material of the light-emitting layer includes core-shell quantum dots, and the core-shell quantum dots have a first shell layer and a second shell layer from the inside to the outside, wherein the material of the first shell layer is ZnSe, and the material of the second shell layer is CdZnS.

[0008] Optionally, in some embodiments of the present application, the fluorescence quantum yield of the core-shell quantum dots is greater than 70%; and / or,

[0009] The thickness of the light-emitting layer is 1 to 1.5 times the average particle size of the core-shell quantum dots; and / or,

[0010] The ratio of the thickness of the first shell layer to the radius of the core of the quantum dot is 0.5 to 2:1; and / or,

[0011] The ratio of the thickness of the second shell layer to the radius of the core of the quantum dot is 0.4 to 2:1.

[0012] Optionally, in some embodiments of the present application, a ligand is connected to the surface of the core-shell quantum dot, and the ligand includes at least one of a substituted or unsubstituted C10-C24 chain organic carboxylic acid and a substituted or unsubstituted C10-C24 chain thiol, wherein the substituent includes at least one of a C1-C8 alkyl, a C1-C8 alkoxy and a halogen;

[0013] In the light-emitting layer, the mass of the ligand accounts for 15-18% of the mass of the material of the light-emitting layer.

[0014] Optionally, in some embodiments of the present application, the molar ratio of the first hole transport material to the second hole transport material is 0.01 to 1:1; and / or,

[0015] The HOMO energy level of the first hole transport material is -5.4 to -6.5 eV; and / or,

[0016] The HOMO energy level of the second hole transport material is -5.3 to -5.5 eV; and / or,

[0017] An absolute value of the HOMO energy level of the first hole transport material is greater than an absolute value of the HOMO energy level of the second hole transport material.

[0018] Optionally, in some embodiments of the present application, the hole transport layer includes a stacked first film layer and a second film layer, the first film layer is arranged close to the light-emitting layer, the material of the first film layer is the first hole transport material, and the material of the second film layer is the second hole transport material.

[0019] Optionally, in some embodiments of the present application, the mobility of the first hole transport material is 2.5×10 -6 ~1×10 -3 cm 2 / Vs; and / or,

[0020] The mobility of the second hole transport material is 2×10 -3 ~100×10 -3 cm 2 / Vs.

[0021] Optionally, in some embodiments of the present application, the first hole transport material includes any one of TCTA, TPD, PVK, CBP, and CBP-V; and / or,

[0022] The second hole transport material includes any one of TFB and V-TPAVCBP:10%OPPI.

[0023] Optionally, in some embodiments of the present application, the light-emitting device further comprises an electron transport layer disposed between the cathode and the light-emitting layer; the mobility of the material of the electron transport layer is 1×10 -3 ~100×10 -3 cm 2 / Vs.

[0024] Optionally, in some embodiments of the present application, the light-emitting device further comprises an electron transport layer disposed between the cathode and the light-emitting layer;

[0025] The average particle size of the material of the electron transport layer is 2 to 12 nm; and / or,

[0026] The material of the electron transport layer includes one or more of metal oxides and doped metal oxides; the metal oxides include ZnO, TiO 2 SnO 2 、ZrO、Al 2 O 3 , WO 3 , HfO 3 、 2 O 3 、ZrSiO 4 、BaTiO 3 、BaZrO 3 One or more of the following; the metal oxide in the doped metal oxide includes ZnO, TiO 2 SnO 2 、ZrO、Al 2 O 3 , WO 3 , HfO 3 、 2 O 3 、ZrSiO 4 、BaTiO 3 、BaZrO 3 The doping elements include one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu.

[0027] Optionally, in some embodiments of the present application, the core material of the core-shell quantum dots is selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds; the II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, Hg At least one of STe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS , SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, At least one of AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from CuInS 2 、CuInSe 2 and AgInS 2 At least one of; and / or,

[0028] The anode and the cathode are independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode. The material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide. The composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO 2 / Ag / TiO 2 、TiO 2 / Al / TiO 2 , ZnS / Ag / ZnS, ZnS / Al / ZnS, the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba; and / or,

[0029] The light emitting device further comprises a hole injection layer disposed between the anode and the hole transport layer, wherein the material of the hole injection layer comprises poly(ethylenedioxythiophene):polystyrene sulfonate, poly[(9,9'-dioctylfluorenyl-2,7-diyl)-CO-(4,4'-(N-(p-butylphenyl))diphenylamine)], polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine, 4-bis[N-(1-naphthyl)-N-phenyl-amino] One or more of biphenyl, 4,4',4"-tri[phenyl(m-tolyl)amino]triphenylamine, 4,4',4"-tri(carbazole-9-yl)triphenylamine, 1,1-bis[(di-4-tolylamino)phenylcyclohexane, 4,4',4"-tri(diphenylamino)triphenylamine doped with tetrafluoro-tetracyano-quinodimethane, p-doped phthalocyanine, F4-TCNQ doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, hexaazatriphenylene-capronitrile.

[0030] Optionally, in some embodiments of the present application, the thickness of the anode is 20 to 200 nm; and / or,

[0031] The thickness of the cathode is 40 to 190 nm; and / or,

[0032] The thickness of the hole transport layer is 30 to 180 nm; and / or,

[0033] The thickness of the electron transport layer is 20 to 180 nm; and / or,

[0034] The light emitting device further comprises a hole injection layer disposed between the anode and the hole transport layer, and the thickness of the hole injection layer is 20-200 nm.

[0035] In a second aspect, the present application further proposes a display device, which includes the light-emitting device described above.

[0036] The technical solution provided by the present application is that the device adopts a hole transport layer that is a mix of two hole transport materials, so that the hole transport layer has the advantages of moderate HOMO energy level and high mobility, which can greatly improve the hole injection level. In order to ensure that this advantage is fully utilized, it is matched with core-shell structure quantum dots with a shell structure of ZnSe / CdZnS, which helps high hole injection to effectively carry out efficient composite luminescence in the light-emitting layer, thereby reducing the probability of the device being charged and improving the luminescence efficiency and life of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0038] Figure 1 is a structural schematic diagram of a light-emitting device proposed in one embodiment of the present application;

[0039] Figure 2 is a structural schematic diagram of a light emitting device proposed in another embodiment of the present application;

[0040] Reference numerals:

[0041] 100 - light-emitting device; 10 - anode; 20 - light-emitting layer; 30 - cathode; 40 - electron transport layer; 50 - hole transport layer; 51 - first film layer; 52 - second film layer; 60 - hole injection layer; 201 - quantum dots. DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0043] In this application, unless otherwise specified, the directional words used, such as "upper" and "lower", refer specifically to the directions of the drawings in the accompanying drawings. In addition, in the description of the specification of this application, the term "including" means "including but not limited to".

[0044] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0045] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0046] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0047] The present application provides a light emitting device 100, which may be a quantum dot light emitting diode (QLED) or the like. Figure 1 The light-emitting device 100 comprises an anode 10, a hole transport layer 50, a light-emitting layer 20, and a cathode 30 which are stacked in sequence, wherein the absolute value of the energy level difference between the hole transport layer 50 and the light-emitting layer 20 is 0.1 to 1.6 eV, and the hole transport layer 50 comprises a first hole transport material and a second hole transport material, and the mobility of the first hole transport material is 2×10 -6 ~1×10 -3 cm 2 / Vs, the mobility of the second hole transport material is greater than or equal to 1×10 -3 cm 2 / Vs; the material of the light-emitting layer 20 includes core-shell quantum dots 201, and the core-shell quantum dots have a first shell layer and a second shell layer from the inside to the outside, wherein the material of the first shell layer is ZnSe, and the material of the second shell layer is CdZnS.

[0048] The technical solution provided by the present application is that the device adopts a hole transport layer 50 that is a mix of two hole transport materials, so that the hole transport layer 50 has the advantages of moderate HOMO energy level and high mobility, which can greatly improve the hole injection level. In order to ensure that this advantage is fully utilized, it is matched with a core-shell structure quantum dot 201 with a shell structure of ZnSe / CdZnS, which helps high hole injection to effectively carry out efficient composite luminescence in the light-emitting layer 20, thereby reducing the probability of the device being charged and improving the luminescence efficiency and life of the device.

[0049] The absolute value of the energy level difference between the hole transport layer 50 and the light-emitting layer 20 is 0.1 to 1.6 eV, for example, 0.1 eV, 0.3 eV, 0.5 eV, 0.7 eV, 0.9 eV, 1.0 eV, 1.1 eV, 1.3 eV, 1.5 eV, 1.6 eV and values ​​between any two of the above values. Within this energy level difference range, the hole injection barrier is reduced, which helps to enhance hole injection. By mixing two hole transport materials, the energy level of the hole transport layer 50 as a whole can be accurately controlled to be at an appropriate position, so that the absolute value of the energy level difference between the hole transport layer 50 and the light-emitting layer 20 is 0.1 to 1.6 eV.

[0050] Specifically, in some embodiments, the HOMO energy level of the first hole transport material is -5.4 to -6.5 eV; for example, it can be -5.4 eV, -5.5 eV, -5.6 eV, -5.7 eV, -5.8 eV, -5.9 eV, -6 eV, -6.1 eV, -6.2 eV, -6.5 eV, and values ​​between any two of the above values. The HOMO energy level of the second hole transport material is -5.3 to -5.5 eV; for example, it can be -5.3 eV, -5.35 eV, -5.4 eV, -5.45 eV, -5.5 eV, and values ​​between any two of the above values.

[0051] In some embodiments, the absolute value of the HOMO energy level of the first hole transport material is greater than the absolute value of the HOMO energy level of the second hole transport material. For example, when the HOMO energy level of the first hole transport material is -5.4 eV, a second hole transport material having a HOMO energy level greater than or equal to -5.3 eV and less than -5.4 eV can be selected.

[0052] The mobility of the first hole transport material is 2×10 -6 ~1×10 -3 cm2 / Vs, for example, can be 2×10 -6 cm 2 / Vs,3×10 -6 cm 2 / Vs,5×10 -6 cm 2 / Vs,8×10 -6 cm 2 / Vs,1×10 -5 cm 2 / Vs,5×10 -5 cm 2 / Vs,1×10 -4 cm 2 / Vs,5×10 -4 cm 2 / Vs,1×10 -3 cm 2 / Vs and a value between any two of the above values; the mobility of the second hole transport material is greater than or equal to 1×10 -3 cm 2 / Vs, for example, can be 1×10 -3 cm 2 / Vs,2×10 -3 cm 2 / Vs,5×10 -3 cm 2 / Vs,10×10 -3 cm 2 / Vs,20×10 -3 cm 2 / Vs,25×10 -3 cm 2 / Vs,30×10 -3 cm 2 / Vs,35×10 - 3 cm 2 / Vs,40×10 -3 cm 2 / Vs,50×10 -3 cm 2 / Vs,60×10 -3 cm 2 / Vs、70×10 -3 cm 2 / Vs,80×10 -3 cm 2 / Vs、90×10 -3 cm 2 / Vs,100×10 -3 cm 2 / Vs and so on.

[0053] Furthermore, in some embodiments, the mobility of the first hole transport material is 2.5×10 -6 ~1×10 -3 cm 2 / Vs; the mobility of the second hole transport material is 2×10 -3 ~100×10 -3 cm 2 / Vs.

[0054] In some embodiments, the molar ratio of the first hole transport material to the second hole transport material is 0.01 to 1:1; for example, 0.01:1, 0.05:1, 0.1:1, 0.11:1, 0.15:1, 0.17:1, 0.2:1, 0.5:1, 1:1 and values ​​between any two of the above values. Within this range, it is helpful to accurately control the energy level and mobility of the hole transport layer 50. Further, in other embodiments, the molar ratio can be 0.1 to 0.2:1.

[0055] The hole transport layer 50 prepared by mixing the above two hole transport materials has both high hole mobility and moderate HOMO energy level, which can ensure high hole injection.

[0056] In specific implementation, the first hole transport material and the second hole transport material can be formed into a film in a blended manner, or the first hole transport material can be used to form a film first, and then the second hole transport material can be used to form a film; or the second hole transport material can be used to form a film first, and then the first hole transport material can be used to form a film. In some embodiments, the absolute value of the HOMO energy level of the first hole transport material is greater than the absolute value of the HOMO energy level of the second hole transport material; Figure 2 As shown, the hole transport layer 50 includes a stacked first film layer 51 and a second film layer 52, wherein the first film layer 51 is arranged close to the light-emitting layer 20, the material of the first film layer 51 is the first hole transport material, and the material of the second film layer 52 is the second hole transport material, so that a step energy level barrier can be formed between the light-emitting layer 20, the first film layer 51, and the second film layer 52, which helps to further reduce the hole injection barrier and enhance hole injection.

[0057] In some embodiments, the first hole transport material includes any one of TCTA, TPD, PVK, CBP, and CBP-V.

[0058] The Chinese name of TCTA is 4,4',4"-tri(carbazole-9-yl)triphenylamine; CAS number is 139092-78-7; HOMO energy level is -5.7eV; hole mobility is 1×10 -5 cm 2 / Vs.

[0059] The Chinese name of TPD is N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine; the CAS number is 122738-21-0; the HOMO energy level is -5.4eV; the hole mobility is 1.1×10 -5 cm 2 / Vs.

[0060] The Chinese name of PVK is poly(9-vinylcarbazole); the CAS number is 25067-59-8; the HOMO energy level is -5.8eV; the hole mobility is 2.5×10 -6 cm 2 / Vs.

[0061] CBP-V is derived from the literature “Inkjet-Printed High-Efficiency Multilayer QLEDs Based on a Novel Crosslinkable Small-Molecule Hole Transport Material”; HOMO level is -6.2eV; hole mobility is 6.6×10 -6 cm 2 / Vs.

[0062] The Chinese name of CBP is 4,4'-bis(9H-carbazole-9-yl)biphenyl, CAS: 58328-31-7; the HOMO energy level is -5.8eV, and the hole mobility is 1.0×10 -3 cm 2 / Vs.

[0063] In some embodiments, the second hole transport material includes any one of TFB, V-TPAVCBP: 10% OPPI.

[0064] The Chinese name of TFB is poly[(9,9'-dioctylfluorenyl-2,7-diyl)-CO-(4,4'-(N-(p-butylphenyl))diphenylamine)]; CAS number: 223569-31-1; HOMO energy level is -5.3 eV; hole mobility is 3×10 -3 cm 2 / Vs.

[0065] V-TPAVCBP: 10% OPPI is derived from the literature "Chemically Doped Hole Transporting Materials with Low Cross-linking Temperature and High Mobility for Solution-Processed Green / Red PHOLEDs"; HOMO level is -5.37 eV; hole mobility is 4.9×10 -3 cm 2 / Vs.

[0066] Generally speaking, low QY quantum dots 201 have short fluorescence lifetime, low luminescence efficiency, and low probability of effective recombination of carriers in them; while high QY quantum dots 201 have fewer defects, which helps to reduce the probability of non-radiative recombination, and high carrier injection can effectively carry out efficient recombination and luminescence in the light-emitting layer 20, thereby reducing the probability of device charge and improving device performance. In order to give full play to the advantages of high hole injection, the luminescence efficiency and life of the device are greatly improved. In some embodiments, the QY of the core-shell quantum dots 201 is greater than 70%, for example, it can be 71%, 75%, 80%, 85%, 90%, 92%, etc.

[0067] In some embodiments, the core-shell quantum dot 201 has a first shell and a second shell from the inside to the outside. The material of the first shell is ZnSe, and the shallow valence band helps to improve hole injection, but its own band gap is relatively moderate, and its ability to bind excitons is relatively weak; the material of the second shell is CdZnS, which not only has a relatively wide band gap, but also has a relatively moderate position of the valence band, which can ensure that the excitons are bound, and improve the hole injection into the luminescent core, thereby improving the carrier recombination efficiency. The two shells work together to effectively reduce the hole injection barrier, which helps to efficiently inject holes into the core of the quantum dot 201.

[0068] In some embodiments, the ratio of the thickness of the first shell layer to the radius of the core of the quantum dot 201 is 0.5 to 2:1; for example, the ratio can be 0.5:1, 0.6:1, 0.8:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.5:1, etc.; this helps to effectively control the binding ability of excitons, which is not only beneficial to reduce the tunneling barrier during carrier injection and promote carrier injection, but also helps to effectively recombine the carriers injected into the core of the quantum dot 201.

[0069] In some embodiments, the ratio of the thickness of the second shell layer to the radius of the core of the quantum dot 201 is 0.4 to 2:1; for example, the ratio can be 0.4:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.3:1, 1.5:1, 1.7:1, 1.8:1, 2:1, etc.; this helps to effectively control the binding ability of excitons and isolate the excitons from the outside world, thereby reducing the probability of excitons being captured by the outside world, while reducing the tunneling barrier during carrier injection and promoting carrier injection.

[0070] In some embodiments, the core material of the quantum dot 201 may be selected from but not limited to at least one of a II-VI compound, an IV-VI compound, a III-V compound, and an I-III-VI compound; as an example, the II-VI compound is selected from but not limited to CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeT e, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from but not limited to SnS, SnSe, SnTe, PbS, PbSe, PbTe, S At least one of nSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe; the III-V group compound is selected from but not limited to GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, Al At least one of NAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI group compound is selected from CuInS 2 、CuInSe2 and AgInS 2 At least one of .

[0071] As an example, the core-shell structured quantum dots 201 may be selected from but not limited to at least one of CdZnSe / ZnSe / CdZnS, CdSe / ZnSe / CdZnS, InP / ZnSe / CdZnS, CdSeS / ZnSe / CdZnS, ZnSe / ZnSe / CdZnS, and ZnSeTe / ZnSe / CdZnS.

[0072] It should be noted that, for the core material of the core-shell structure quantum dots or the shell material of the core-shell structure quantum dots, the chemical formula provided only indicates the elemental composition, but does not indicate the content of each element. For example, CdZnS only indicates that it is composed of three elements: Cd, Zn and S. If the content of each element is indicated, it corresponds to Cd x Zn 1-x S, 0 <x<1。

[0073] In addition, in some embodiments, the thickness of the light-emitting layer 20 is 1 to 1.5 times the average particle size of the quantum dots 201; for example, it can be 1 times, 1.1 times, 1.2 times, 1.3 times, 1.4 times, 1.5 times, and values ​​between any two of the above values. Within this range, the light-emitting layer 20 prepared is roughly a single-layer film, that is, in the thickness direction, the light-emitting layer 20 is roughly formed by a layer of quantum dots 201. The number of layers of quantum dots 201 significantly affects the transmission path of carriers. The more layers there are, the longer the path for carriers to tunnel through the quantum dots 201 (it is necessary to tunnel through multiple quantum dots 201 and multiple ligands), which is more unfavorable for the transmission of carriers. By controlling the light-emitting layer 20 to be a single-layer film, the tunneling barrier of electrons and holes can be greatly reduced, the migration path of electrons and holes can be reduced, the transmission rate of carriers can be increased, and the recombination efficiency of carriers can be improved.

[0074] In some embodiments, the average particle size of the quantum dots 201 is 11-16 nm, for example, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, and values ​​between any two of the above values, so that the quantum dots 201 are more conducive to forming a single layer film. Correspondingly, the thickness of the light-emitting layer 20 is 11-24 nm, for example, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 20 nm, 22 nm, 23 nm, 24 nm, and values ​​between any two of the above values.

[0075] In some embodiments, the shape of the quantum dot 201 includes but is not limited to sphere, cube, tetrahedron, column, tetrapod, octapod, flake, etc.

[0076] In some embodiments, the core-shell quantum dot surface is also connected to a ligand, and the raw material of the ligand includes at least one of substituted or unsubstituted C10-C24 chain organic carboxylic acid, substituted or unsubstituted C10-C24 chain organic amine, substituted or unsubstituted C10-C24 chain thiol, substituted or unsubstituted C10-C24 chain organic phosphine, substituted or unsubstituted C10-C24 chain organic phosphine oxide, and halide. Wherein, "substituted or unsubstituted" means that the defined group can be substituted or unsubstituted. When the defined group is substituted, it should be understood that the defined group can be substituted by one or more substituents; the substituent is selected from at least one of C1-C8 alkyl, C1-C8 alkoxy and halogen; optionally, the substituent is selected from at least one of C1-C5 alkyl, C1-C5 alkoxy and halogen; or the substituent is selected from at least one of C1-C3 alkyl, C1-C3 alkoxy and halogen. The halogen refers to -F, -Cl, -Br or -I. Specifically, the organic carboxylic acid includes one or more of decadecanoic acid (CAS: 334-48-5), undecenoic acid (CAS: 112-38-9), tetradecanoic acid (CAS: 544-63-8), oleic acid (CAS: 112-80-1) and stearic acid (CAS: 57-11-4); the organic amine includes one or more of oleylamine (CAS: 112-90-3) and octadecylamine (CAS: 124-30-1); the organic (oxygen) phosphine includes tris(II)-1-butylamine (CAS: 112-90-3); One or more of octylphosphine (CAS: 4731-53-7) and trioctylphosphine oxide (CAS: 78-50-2); the thiol includes one or more of n-octylmercaptan (CAS: 111-88-6), dodecanethiol (CAS: 112-55-0) and octadecanethiol (CAS: 2885-00-9); the halide is selected from one or more of hydrofluoric acid, hydrochloric acid, hydroiodic acid, hydrobromic acid, metal fluoride, metal chloride, metal iodide and metal bromide.

[0077] The mass of the ligand accounts for 15% to 20% of the total mass of the core-shell quantum dots 201 and the ligand, for example, it can be 15%, 16%, 17%, 18%, 19%, 20% and values ​​between any two of the above values. Within this range, it helps to improve the dispersibility of the quantum dots 201 and enhance its film-forming effect.

[0078] In some embodiments, at least a portion of the ligands are strong coordination ligands, and the raw materials of the strong coordination ligands are selected from one or more of substituted or unsubstituted C1-C24 chain thiols and halides. The strong coordination ligands can form strong coordination bonds with the surface cations of the core-shell quantum dots 201, are not easy to fall off, and help improve the film-forming effect of the light-emitting layer 20. It can be understood that in some embodiments, in addition to the first ligand, the ligands also contain some ligands with relatively weak coordination effects (weak ligands), including but not limited to organic carboxylic acids, organic amines, etc.

[0079] Furthermore, the mass percentage of the strong coordinating ligand is 15% to 20%, for example, it can be 15%, 16%, 17%, 18%, 19%, 20% and values ​​between any two of the above values. When the content of the strongly coordinating ligand connected to the surface of the quantum dot 201 is relatively high, its film-forming property is relatively good. In this way, when preparing a single-layer film luminous layer 20, it helps to improve the film-forming quality of the single-layer film, ensure that the luminous layer 20 has a good film-forming effect, help to improve the interface contact between the luminous layer 20 and the adjacent film layer in the device, and thus help to simultaneously improve the luminous efficiency and service life of the device.

[0080] Furthermore, in some embodiments, when the anions on the surface of the quantum dot 201 include sulfur atoms, for example, when the quantum dot 201 is CdS or ZnSe / CdZnS, and the ligand is a thiol ligand, then when preparing the quantum dot 201, the thiol compound can be added as an anion source, and the S atoms on the ligand can be directly coordinated and connected with the cations on the surface of the quantum dot 201, or directly act as S atoms on the shell surface of the quantum dot 201 and be directly embedded in the shell, which helps to further improve the coordination effect of the ligand and reduce the probability of shedding.

[0081] It can be understood that the content of the ligand and the strong coordinating ligand can be detected by nuclear magnetic resonance and thermal gravimetric test, and the number of strong coordinating ligands on the surface of quantum dot 201 can be introduced during the synthesis process or introduced by ligand exchange. First, nuclear magnetic resonance can measure the content of specific ligands on the surface of quantum dot 201. Secondly, thermal gravimetric test can determine the total content of ligands on the surface of quantum dot 201. Finally, the difference between the two ligands is the content of other ligands. The specific test method for determining the content of specific ligands on the surface of quantum dot 201 by nuclear magnetic resonance is as follows: dissolve quantum dot 201 in a deuterated reagent, and add a specific amount of internal standard as a reference, and calculate the ratio of the chemical shift integrated area of ​​the ligand of quantum dot 201 to the chemical shift integrated area of ​​the internal standard, so as to quantify the ligand content to be measured. The thermal gravimetric test detection method is as follows: heat the quantum dot 201 material until its mass no longer changes, and record the weight loss W of the material when it starts to lose weight to the temperature where the strong coordinating ligand falls off. 1, and record the weight loss W of the material from the beginning of weight loss to the time when its mass no longer changes 2 , then W 2 is the content of ligand, W 2 -W 1 is the content of strong coordinating ligands.

[0082] NMR and thermal gravimetric methods can also be used simultaneously, for example, to determine the content of specific quantum dot 201 surface ligands oleic acid (weak ligand) and thiol (thiol as a strong coordinating ligand). The specific test method is as follows: First, dissolve quantum dot 201 in deuterated toluene, use ferrocene as an internal standard (the amount added is rated, the chemical shift is 3.8-4.0ppm), and measure the chemical shift of quantum dot 201 ligand at 5.4-5.8ppm. Finally, divide the integral area of ​​the chemical shift of the ligand at 5.4-5.8ppm by the integral area of ​​the chemical shift of the internal standard at 3.8-4.0ppm to obtain the content of oleic acid ligand. Second, for example, measure the thermal gravimetric loss of quantum dot 201 at 20-600℃, and record the weight loss at 100℃-500℃, which is the total content of ligands on the surface of quantum dot 201. Finally, subtract the oleic acid ligand content from the total ligand content to obtain the thiol ligand content.

[0083] In some embodiments, the light emitting device 100 further includes an electron transport layer 40 disposed between the cathode 30 and the light emitting layer 20. The mobility of the material of the electron transport layer 40 is 1×10 -3 ~100×10 -3 cm 2 / Vs. For example, 1×10 - 3 cm 2 / Vs,2×10 -3 cm 2 / Vs,5×10 -3 cm 2 / Vs,10×10 -3 cm 2 / Vs,12×10 -3 cm 2 / Vs,15×10 -3 cm 2 / Vs,18×10 -3 cm 2 / Vs,20×10 -3 cm 2 / Vs,25×10 -3 cm 2 / Vs,30×10 -3 cm 2 / Vs,35×10 -3 cm 2 / Vs,40×10 - 3 cm 2 / Vs,50×10 -3 cm 2 / Vs,60×10 -3 cm 2 / Vs、70×10 -3 cm 2 / Vs,80×10 -3 cm 2 / Vs、90×10 -3 cm 2 / Vs,100×10 -3 cm 2 / Vs and the value between any two of the above values. When the hole transport layer 50 has both high mobility and moderate energy level and high hole injection, it is matched with an electron transport material with high electron injection, which helps to improve the balance of carriers in the device while ensuring high hole injection, and helps the high-efficiency recombination of carriers in the light-emitting layer 20, thereby improving the overall carrier concentration. When it is matched with quantum dots 201 with high luminous efficiency, single-layer film, and shell structure of ZnSe / CdZnS, it further promotes the high-efficiency recombination of carriers in the light-emitting layer 20, greatly improving the luminous efficiency and life of the device.

[0084] In some embodiments, the average particle size of the material of the electron transport layer 40 is 2 to 12 nm, for example, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 8 nm, 10 nm, 11 nm, 12 nm, and values ​​between any two of the above values. The electron transport material with such a particle size is easy to be made into a film with uniform film thickness and dense film during film formation, which helps to improve the film quality.

[0085] In some embodiments, the material of the electron transport layer 40 is, but is not limited to, one or more of metal oxides and doped metal oxides. As an example, the metal oxide is, but is not limited to, ZnO, TiO 2 SnO 2 、ZrO、Al 2 O 3 , WO 3 , HfO 3 、 2 O 3 、ZrSiO 4 、BaTiO 3 、BaZrO 3 One or more of; the metal oxide in the doped metal oxide includes but is not limited to ZnO, TiO 2 SnO 2 、ZrO、Al2 O 3 , WO 3 , HfO 3 、 2 O 3 、ZrSiO 4 、BaTiO 3 、BaZrO 3 The doping elements include, but are not limited to, one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu.

[0086] In addition, in some embodiments, the surface of the electron transport material may be connected with a ligand, and the ligand includes one or more of an acid ligand, an amine ligand, and a thiol ligand. Specifically, the raw materials of the ligand include but are not limited to one or more of oleic acid, oleylamine, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, and octadecanoic acid.

[0087] The metal oxide MO or the doped metal oxide MAO can be obtained by mixing the cation source, the alkali source and the solvent, wherein M is a metal element and A is a doping element. Specifically, when the material to be prepared is a metal oxide, the cation source is a metal salt that can provide the M metal element, such as zinc acetate, etc.; when the material to be prepared is a doped metal oxide, the cation source includes a metal salt that can provide the M metal element and a metal salt that can provide the A doping element, such as zinc acetate, magnesium acetate, etc.; the alkali source includes one or more of an organic base and an inorganic base, the organic base is selected from one or more of hexamethylenetetramine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, and urea, and the inorganic base is selected from one or more of sodium hydroxide, lithium hydroxide, potassium hydroxide, calcium hydroxide, ammonium hydroxide, sodium carbonate, and potassium carbonate; the solvent includes alcohols or dimethyl sulfoxide (DMSO). When preparing the electron transport material, the mobility of the electron transport layer 40 material can be precisely controlled by adjusting the type and content of the doping element, the amount of alkali source added, the post-treatment conditions and other parameters. In actual operation, the preparation can be made with reference to the method for regulating the mobility of the electron transport layer 40 material commonly used in the art. Taking the method of regulating the amount of alkali source added to control the electron mobility as an example, in some embodiments, the electron transport layer 40 material is ZnO. In order to adjust its electron mobility, tetramethylammonium hydroxide can be used as the alkali source. When preparing ZnO, the molar ratio of ZnO and tetramethylammonium hydroxide is controlled to be 1:1.5, and a mobility of 0.1×10 -3 cm 2 / Vs ZnO nanoparticles; the molar ratio of ZnO and tetramethylammonium hydroxide can also be controlled to 1:0.5, and a mobility of 5×10 -3 cm 2 / Vs of ZnO nanoparticles.

[0088] In some embodiments, the anode 10 is independently selected from a doped metal oxide particle electrode, a composite electrode of a metal and a metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode. The material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide. The composite electrode of the metal and the metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO 2 / Ag / TiO 2 、TiO 2 / Al / TiO 2 , ZnS / Ag / ZnS, ZnS / Al / ZnS, the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

[0089] In some embodiments, the cathode 30 is independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode. The material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide. The composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO 2 / Ag / TiO 2 、TiO 2 / Al / TiO 2 , ZnS / Ag / ZnS, ZnS / Al / ZnS, the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba.

[0090] In some embodiments, the light-emitting device 100 further includes a hole injection layer 60 disposed between the anode 10 and the hole transport layer 50, and the material of the hole injection layer 60 includes poly(ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), poly[(9,9'-dioctylfluorenyl-2,7-diyl)-CO-(4,4'-(N-(p-butylphenyl))diphenylamine)] (TFB), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), 4,4',4"-tri[phenyl One or more of (m-tolyl)amino]triphenylamine (m-MTDATA), 4,4',4"-tri(carbazol-9-yl)triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane (TAPC), 4,4',4"-tri(diphenylamino)triphenylamine (TDATA) doped with tetrafluoro-tetracyano-quinodimethane (F4-TCNQ), p-doped phthalocyanine (e.g., F4-TCNQ-doped zinc phthalocyanine (ZnPc)), F4-TCNQ-doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), and hexaazatriphenylene-capronitrile (HAT-CN).

[0091] In some embodiments, the thickness of the anode 10 is 20-200 nm; for example, it can be 20-40 nm, 30-60 nm, 50-80 nm, 55-90 nm, 70-100 nm, 90-120 nm, 110-140 nm, 130-150 nm, 140-170 nm, 160-200 nm, and the like.

[0092] In some embodiments, the thickness of the cathode 30 is 40-190 nm; for example, it can be 40-60 nm, 50-80 nm, 55-90 nm, 70-100 nm, 90-120 nm, 110-140 nm, 130-150 nm, 140-170 nm, 160-190 nm, and the like.

[0093] In some embodiments, the thickness of the hole transport layer 50 is 30 to 180 nm; for example, it can be 30 to 40 nm, 35 to 60 nm, 50 to 80 nm, 55 to 90 nm, 70 to 100 nm, 90 to 120 nm, 110 to 140 nm, 130 to 150 nm, 140 to 170 nm, 160 to 180 nm, and the like.

[0094] In some embodiments, the thickness of the electron transport layer 40 is 20-180 nm; for example, it can be 20-40 nm, 30-60 nm, 50-80 nm, 55-90 nm, 70-100 nm, 90-120 nm, 110-140 nm, 130-150 nm, 140-170 nm, 160-180 nm, and the like.

[0095] In some embodiments, the thickness of the hole injection layer 60 is 20-200 nm; for example, it can be 20-40 nm, 30-60 nm, 50-80 nm, 55-90 nm, 70-100 nm, 90-120 nm, 110-140 nm, 130-150 nm, 140-170 nm, 160-200 nm, and the like.

[0096] It is understandable that the light emitting device 100 may also be provided with some functional layers conventionally used in the light emitting device 100 to help improve the performance of the light emitting device 100, such as an electron blocking layer, a hole blocking layer, an interface modification layer, etc.

[0097] It can be understood that the light emitting device 100 can be an upright light emitting device or an inverted light emitting device.

[0098] Based on the above embodiments, the present application further proposes a method for preparing a light emitting device 100, which is used to prepare the above light emitting device 100. In some embodiments, the light emitting device 100 may be a positive light emitting device, and accordingly, the preparation method includes:

[0099] S10a, providing an anode 10;

[0100] S20a, sequentially disposing a hole functional layer, a light emitting layer 20 and an electron transport layer 40 on the anode 10;

[0101] S30 a , disposing the cathode 30 on the electron transport layer 40 .

[0102] In some other embodiments, the light emitting device 100 may be an inverted light emitting device, and accordingly, the preparation method includes:

[0103] S10b, providing a cathode 30;

[0104] S20b, sequentially disposing an electron transport layer 40, a light emitting layer 20 and a hole functional layer on the anode 10;

[0105] S30b, disposing the anode 10 on the electron transport layer 40 .

[0106] In steps S20a and S20b, the hole functional layer includes the hole transport layer 50 , or includes the hole transport layer 50 and the hole injection layer 60 . When the hole functional layer includes the hole transport layer 50 and the hole injection layer 60 , the hole injection layer 60 is disposed closer to the anode 10 .

[0107] In the preparation method of the light-emitting device 100, the preparation method of the anode 10, the light-emitting layer 20, the electron transport layer 40, the hole transport layer 50, the hole injection layer 60 and the cathode 30 can be achieved by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction method, anode 10 oxidation method, electrolytic deposition method, coprecipitation method. Physical methods include physical plating method and solution method, among which physical plating method includes: thermal evaporation coating method, electron beam evaporation coating method, magnetron sputtering method, multi-arc ion plating method, physical vapor deposition method, atomic layer deposition method, pulsed laser deposition method, etc.; solution method can be spin coating method, printing method, inkjet printing method, doctor blade method, printing method, dip pulling method, immersion method, spray coating method, roll coating method, casting method, slit coating method and strip coating method, etc.

[0108] The materials of the anode 10 , the light emitting layer 20 , the electron transport layer 40 , the hole transport layer 50 , the hole injection layer 60 and the cathode 30 are as described above and will not be described in detail here.

[0109] In some embodiments, after the light emitting device 100 is prepared, the step of packaging the light emitting device 100 is further included. The packaging process can be performed by a common machine packaging or by manual packaging. Preferably, in the environment of the packaging process, the oxygen content and the water content are both less than 0.1 ppm to ensure the stability of the light emitting device 100.

[0110] In addition, the present application also relates to a display device, which includes the light-emitting device 100. The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptop computers, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, wherein the smart wearable device can be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.

[0111] The technical scheme and technical effects of the present application are described in detail below through specific embodiments and comparative examples. The following embodiments are only some embodiments of the present application and do not specifically limit the present application.

[0112] Example 1

[0113] This example aims to investigate the effect of the number of quantum dot layers on device performance

[0114] Experimental Group 1

[0115] The structure of the QLED device in this experimental group is: anode, hole injection layer, hole transport layer, light-emitting layer, electron transport layer and cathode stacked from bottom to top. The thickness of each layer is: anode 130nm

[0116] , hole injection layer 120nm, hole transport layer 100nm, light emitting layer 15nm, electron transport layer 70nm, cathode 80nm.

[0117] (1) A glass substrate is provided, and ITO is evaporated on the glass substrate to form an anode.

[0118] (2) Spin coating a PEDOT:PSS material (a commercial product with a doping ratio of 1:6 and a solute content of 1.5 wt%) on the anode and heating at 150° C. for 15 min to obtain a hole injection layer.

[0119] (3) Transfer the substrate obtained in step (2) to a nitrogen atmosphere, spin-coat the first hole transport material on the hole injection layer, and heat at 150°C for 15 min to obtain a first film layer with a thickness of 50 nm; then spin-coat the second hole transport material on the first hole transport layer, and heat at 150°C for 15 min to obtain a second film layer with a thickness of 50 nm; the first film layer and the second film layer together constitute the hole transport layer. The first hole transport material is TCTA, and the HOMO energy level of TCTA is -5.7 eV and the mobility is 1×10 -5 cm 2 / Vs, the second hole transport material is TFB, the HOMO level of TFB is -5.3eV, and the mobility is 3×10 -3 cm 2 / Vs.

[0120] (4) Spin coating an octane solution of quantum dot material on the hole transport layer, and heating at 80° C. for 10 min to obtain a light-emitting layer; wherein the quantum dot material is red quantum dots CdSeS / ZnSe / CdZnS, with a QY of 90%, an average particle size of 15 nm, a surface ligand of dodecanethiol, a mass content of dodecanethiol on the surface of the quantum dots of 16%, and a ratio of the thickness of the first shell layer ZnSe to the core radius of 1:1, and a ratio of the thickness of the second shell layer CdZnS to the core radius of 1:1; during spin coating, the spin coating speed is controlled to be 2000 rpm, the time is 30 s, and the concentration of the quantum dot material in the octane solution of the quantum dot material is 15 mg / ml, so as to control the light-emitting layer to be a single layer film.

[0121] (5) An electron transport layer is prepared on the light-emitting layer; wherein the material of the electron transport layer is ZnO, and its electron mobility is 10×10 -3 cm2 / Vs. The electron mobility is 10×10 -3 cm 2 The preparation method of the electron transport layer of / Vs is as follows: weigh 1 mmol of Zn(Ac) 2 ·2H 2 O and 10ml DMSO are placed in a three-necked flask, and then stirred at 25°C until completely dissolved to obtain the first solution; 0.5mmol tetramethylammonium hydroxide is dissolved in 10ml ethanol to obtain the second solution; then the second solution is slowly added to the first solution; after the reaction is completed, ethyl acetate is added to precipitate, centrifuge, and the supernatant is discarded; anhydrous ethanol is added to dissolve, and then ethyl acetate is added to precipitate and centrifuge. Repeat the above steps twice to obtain ZnO nanoparticles. The ZnO nanoparticles are dispersed in ethanol, spin-coated on the light-emitting layer to form a solid film, and then placed in an oxygen atmosphere and UV-treated for 3min at 365nm and 1200W power to obtain an electron mobility of 10×10 -3 cm 2 / Vs electron transport layer.

[0122] (6) Placing the substrate obtained in step (5) in a vapor deposition chamber, vapor-depositing Ag on the electron transport layer to obtain a cathode, and encapsulating to obtain a QLED device.

[0123] Control group 1

[0124] The control group 1 scheme is basically the same as the experimental group 1, except that in the control group, the light-emitting layer is a double-layer film, and accordingly, in step (4), the average particle size of the quantum dot material is 15 nm; during spin coating, the spin coating speed is controlled to be 2000 rpm, the time is 30 s, and the concentration of the quantum dot material in the n-octane solution of the quantum dot material is 25 mg / ml, so as to control the light-emitting layer to be a double-layer film. The other steps and parameters are the same as those of the experimental group 1.

[0125] Control group 2

[0126] The control group 2 scheme is basically the same as the experimental group 1, except that in the control group, the light-emitting layer is a four-layer film, and accordingly, in step (4), the average particle size of the quantum dot material is 15 nm; during spin coating, the spin coating speed is controlled to be 2000 rpm, the time is 30 s, and the concentration of the quantum dot material in the n-octane solution of the quantum dot material is 43 mg / ml, so as to control the light-emitting layer to be a four-layer film. The other steps and parameters are the same as those of the experimental group 1.

[0127] (i) Take the semi-finished device obtained in step (4) during the preparation of experimental group 1, control group 1 and control group 2, wherein the top layer of the semi-finished device is the light-emitting layer. The roughness of the light-emitting layer is examined by AFM to evaluate its film-forming effect, and the results are recorded in Table 1.

[0128] (ii) Take the devices made in experimental group 1, control group 1 and control group 2, and place the devices under 120°C for 15 minutes for heat treatment to accelerate the forward aging of the devices. Then, perform subsequent performance tests on the devices after the heat treatment, and record the results in Table 1. The detection method is as follows:

[0129] (1) The detection method of external quantum efficiency EQE is: the ratio of the number of electron-hole pairs injected into quantum dots to the number of emitted photons, the unit is %, which is an important parameter to measure the quality of electrophotoelectric devices and can be obtained by measuring with EQE optical testing instruments. The specific calculation formula is as follows:

[0130]

[0131] Among them, η e is the light output coupling efficiency, η γ is the ratio of the number of recombined carriers to the number of injected carriers, x is the ratio of the number of excitons that generate photons to the total number of excitons, K R is the radiation process rate, K NR is the rate of the non-radiative process.

[0132] Test conditions: carried out at room temperature, air humidity is 30-60%.

[0133] (2) The test method for life T95@1000nit is:

[0134] The time required for the device to reduce its brightness to a certain percentage of the maximum brightness when driven by a constant current or voltage. The time it takes for the brightness to drop to 95% of the maximum brightness is defined as T95, and this life is the measured life. In order to shorten the test cycle, the device life test is usually carried out at high brightness by accelerating device aging, and the life under high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula. For example, the life under 1000nit is calculated as T95@1000nit. The specific calculation formula is as follows:

[0135]

[0136] Among them, T95 L For lifespan at low brightness, T95 H is the measured lifetime under high brightness, L H To accelerate the device to the highest brightness, L L is 1000nit, A is the acceleration factor, and this experiment measured the lifespan of several groups of red QLED devices at rated brightness and found that the A value was 1.7.

[0137] Table 1

[0138]

[0139] It can be seen from the above table:

[0140] Experimental group 1 has a smaller roughness, indicating that its film-forming effect is good. At the same time, compared with the control group, experimental group 1 has the highest EQE and T95@1000nit, indicating that when the hole transport material has both a deep HOMO energy level and a high mobility, the carrier injection of the single-layer quantum dot film is more balanced than that of the double-layer film and the multi-layer film, showing a higher EQE and a longer device life; it also shows that for the device with the following combination design: QY greater than 70%, the shell structure of ZnSe / CdZnS core-shell quantum dots, the HOMO energy level is -5.4~-6.5eV, and the mobility is 2×10 -6 ~1×10 -3 cm 2 / Vs of the first hole transport material and the HOMO energy level is -5.3 to -5.5 eV, and the mobility is greater than or equal to 1×10 -3 cm 2 / Vs of the second hole transport material mixed with the hole transport material and the mobility is 1×10 -3 ~100×10 -3 cm 2 / Vs electron transport material; the single-layer film is more compatible with the above-mentioned design, which helps to significantly improve the life of the device while ensuring the luminous efficiency.

[0141] Example 2

[0142] This example aims to investigate the effect of the quantum dot shell structure on device performance.

[0143] The schemes of control groups 3 to 6 are basically the same as those of experimental group 1, with the only difference being that in each control group, the quantum dot materials used in the light-emitting layer are changed to the materials listed in Table 2 below.

[0144] Performance tests were performed on experimental group 1 and control groups 3 to 6, and the results are recorded in Table 2.

[0145] Table 2

[0146] Part Number First Shell Second Shell QY(%) EQE(%) <![CDATA[T95 1000nit (hrs)]]> Experimental Group 1 ZnSe CdZ 90 24 3960 Control group 3 CdZ ZnS 90 20 848 Control group 4 CdZnSeS CdZ 80 18 634 Control group 5 ZnS CdZ 78 17 1750 Control group 6 ZnS ZnS 86 16 620

[0147] As can be seen from the table above, for devices with the same hole transport layer and electron transport layer design, when the shell structure of the light-emitting layer material is changed from ZnSe / CdZnS to other shell structures, the device life is greatly reduced. This shows that compared with other wide-bandgap shell materials, when the first shell is ZnSe and the second shell is CdZnS, holes can be better injected into the shell for effective recombination, which is manifested as a higher EQE. Moreover, this combination of shells can effectively improve the effective recombination of carriers in the device, which is manifested as a longer device life.

[0148] Example 3

[0149] This example aims to investigate the effect of the size of the quantum dots QY on the device performance.

[0150] This embodiment also sets up experimental group 2, control group 7, and control group 8. Among them:

[0151] The experimental group or control group scheme is basically the same as experimental group 1, the only difference is that in each experimental group or control group, the quantum dot material used in the light-emitting layer is changed to the material with QY defined in the following Table 3. In specific implementation, QY can be changed by adjusting the thickness of the second shell layer.

[0152] Performance tests were performed on experimental groups 1-2 and control groups 7-8, and the results are recorded in Table 3.

[0153] Table 3

[0154]

[0155] As can be seen from the table above, experimental groups 1 and 2 have higher EQE and T95 1000nit , indicating that when the hole transport layer has both deep HOMO energy level and high mobility, the light-emitting layer uses single-layer film quantum dots and the quantum dot shell structure is ZnSe / CdZnS, when the light-emitting layer material is changed from a material with QY greater than 70% to a material with QY equal to or less than 70%, the device life and luminous efficiency drop significantly. Obviously, compared with quantum dot materials with QY equal to or less than 70%, when selecting materials with QY greater than 70%, the device design optimization effect is better, which helps to improve the EQE and life of the device.

[0156] Example 4

[0157] This example aims to investigate the effect of hole transport materials on device performance.

[0158] This embodiment also sets up experimental group 3 and control groups 9 to 12. Among them:

[0159] The experimental group or control group scheme is basically the same as that of experimental group 1, except that in each experimental group or control group, the hole transport material used in the hole transport layer is changed to the material in Table 4 below.

[0160] Performance tests were performed on experimental group 3 and control groups 9-12, and the results are recorded in Table 4.

[0161] Table 4

[0162]

[0163]

[0164] It can be seen from the above table that the experimental group exhibits higher luminous efficiency and lifetime than the control group, indicating that the materials provided by the experimental group are more compatible with the device provided in this embodiment than the materials provided by the control group. Obviously, for the single-layer film luminescent layer prepared by using quantum dots with a QY greater than 70% and a shell layer of ZnSe / CdZnS, and the electron mobility of 1×10 -3 ~100×10 -3 cm 2 For devices with electron transport layers made of materials with a HOMO energy level of -5.4 to -6.5 eV and a mobility of 2×10 -6 ~1×10 -3 cm 2 The first hole transport material with a HOMO energy level of -5.3 to -5.5 eV and a mobility of 2×10 -3 ~100×10 -3 cm 2 When the second hole transport material with a specific impedance of 100 W / mA is mixed with other materials, the carrier balance in the device is better, which helps to significantly improve the efficiency of the device.

[0165] Example 5

[0166] This example aims to investigate the effect of the mobility of the electron transport material on the device performance.

[0167] This embodiment further sets up a control group 13 and a control group 14. Among them:

[0168] The control group scheme is basically the same as the experimental group 1, the only difference is that in each control group, the electron transport material used in the electron transport layer is changed to the material in the following Table 6.

[0169] The mobility is 0.05×10 -3 The preparation method of the ZnMgO electron transport layer is as follows: weigh 0.83 mmol of Zn(Ac) 2 ·2H 2 O, 0.17 mmol Mg(Ac)2 ·4H 2 O and 10ml DMSO were placed in a three-necked flask, and then stirred at 25°C until completely dissolved to obtain the first solution; 1.5mmol tetramethylammonium hydroxide was dissolved in 10ml ethanol to obtain the second solution; then the second solution was slowly added dropwise to the first solution; after the reaction was completed, ethyl acetate was added to precipitate, centrifuged, and the supernatant was discarded; anhydrous ethanol was added to dissolve, and then ethyl acetate was added to precipitate and centrifuged. Repeat the above steps twice to obtain a mobility of 0.05×10 -3 The ZnMgO nanoparticles were dispersed in ethanol to prepare a 30 mg / ml ZnMgO ethanol solution, which was spin-coated on the light-emitting layer and heated at 100°C for 8 min to form an electron transport layer.

[0170] The mobility is 200×10 -3 The preparation method of the ZnO electron transport layer is as follows: the mobility of the experimental group 1 is 10×10 -3 The preparation method of the electron transport layer is basically the same, the only difference is that the treatment time during UV irradiation after the solid film is obtained is changed from 3 minutes to 30 minutes, and other parameters and steps remain unchanged.

[0171] Performance tests were performed on experimental group 1, control group 13 and control group 14, and the results are recorded in Table 5.

[0172] Table 5

[0173]

[0174] As can be seen from the above table, compared with the control group, the experimental group exhibits higher luminous efficiency and lifespan, indicating that compared with the materials provided by the control group, the materials provided by the experimental group are more compatible with the device provided in this embodiment. Obviously, for the single-layer film luminescent layer prepared by using quantum dots with QY greater than 70% and a shell layer of ZnSe / CdZnS, and the hole transport layer using a HOMO energy level of -5.4 to -6.5 eV and a mobility of 2×10 -6 ~1×10 -3 cm 2 The first hole transport material with a HOMO energy level of -5.3 to -5.5 eV and a mobility of 2×10 -3 ~100×10 -3 cm 2 For a device with a second hole transport material mixed with a Vs, an electron mobility of 1×10 -3 ~100×10 -3 cm 2 / Vs materials are used to prepare the electron transport layer, the carrier balance in the device is better, which helps to significantly improve the efficiency of the device.

[0175] The light-emitting device and display device provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A light emitting device, characterized in that: The invention comprises an anode, a hole transport layer, a light-emitting layer, and a cathode which are stacked in sequence, wherein the absolute value of the energy level difference between the hole transport layer and the light-emitting layer is 0.1 to 1.6 eV, and the hole transport layer comprises a first hole transport material and a second hole transport material, and the mobility of the first hole transport material is 2×10 -6 ~1×10 -3 cm 2 / Vs, the mobility of the second hole transport material is greater than or equal to 1×10 -3 cm 2 / Vs; The material of the light-emitting layer includes core-shell quantum dots, and the core-shell quantum dots have a first shell layer and a second shell layer from the inside to the outside, wherein the material of the first shell layer is ZnSe, and the material of the second shell layer is CdZnS.

2. The light emitting device according to claim 1, characterized in that: The fluorescence quantum yield of the core-shell quantum dots is greater than 70%; and / or, The thickness of the light-emitting layer is 1 to 1.5 times the average particle size of the core-shell quantum dots; and / or, The ratio of the thickness of the first shell layer to the radius of the core of the quantum dot is 0.5 to 2:1; and / or, The ratio of the thickness of the second shell layer to the radius of the core of the quantum dot is 0.4 to 2:

1.

3. The light emitting device according to claim 1, characterized in that: The molar ratio of the first hole transport material to the second hole transport material is 0.01 to 1:1; and / or, The HOMO energy level of the first hole transport material is -5.4 to -6.5 eV; and / or, The HOMO energy level of the second hole transport material is -5.3 to -5.5 eV; and / or, An absolute value of the HOMO energy level of the first hole transport material is greater than an absolute value of the HOMO energy level of the second hole transport material.

4. The light emitting device according to claim 3, characterized in that: The hole transport layer includes a first film layer and a second film layer stacked together, the first film layer is arranged close to the light-emitting layer, the material of the first film layer is the first hole transport material, and the material of the second film layer is the second hole transport material.

5. The light emitting device according to claim 3, characterized in that: The mobility of the first hole transport material is 2.5×10 -6 ~1×10 -3 cm 2 / Vs; and / or, The mobility of the second hole transport material is 2×10 -3 ~100×10 -3 cm 2 / Vs.

6. The light emitting device according to claim 5, characterized in that: The first hole transport material includes any one of TCTA, TPD, PVK, CBP, and CBP-V; and / or, The second hole transport material includes any one of TFB and V-TPAVCBP:10%OPPI.

7. The light emitting device according to claim 2, characterized in that: The light emitting device further comprises an electron transport layer disposed between the cathode and the light emitting layer; The mobility of the material of the electron transport layer is 1×10 -3 ~100×10 -3 cm 2 / Vs; and / or, The average particle size of the material of the electron transport layer is 2 to 12 nm; and / or, The material of the electron transport layer includes one or more of metal oxides and doped metal oxides; the metal oxide includes one or more of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3; the metal oxide in the doped metal oxide includes multiple of ZnO, TiO2, SnO2, ZrO, Al2O3, WO3, HfO3, Ta2O3, ZrSiO4, BaTiO3, and BaZrO3, and the doping elements include one or more of Al, Mg, Li, In, Ga, Cd, Cs, and Cu.

8. The light emitting device according to claim 1, characterized in that: The anode and the cathode are independently selected from a doped metal oxide particle electrode, a composite electrode of metal and metal oxide, a graphene electrode, a carbon nanotube electrode, a metal electrode or an alloy electrode; the material of the doped metal oxide particle electrode is selected from one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide; the composite electrode of metal and metal oxide is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS; the material of the metal electrode is selected from one or more of Ag, Al, Cu, Mo, Au, Pt, Si, Ca, Mg and Ba; and / or, The light emitting device further comprises a hole injection layer disposed between the anode and the hole transport layer, wherein the material of the hole injection layer comprises poly(ethylenedioxythiophene):polystyrene sulfonate, poly[(9,9'-dioctylfluorenyl-2,7-diyl)-CO-(4,4'-(N-(p-butylphenyl))diphenylamine)], polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine, 4-bis[N-(1-naphthyl)-N-phenyl-amino] One or more of biphenyl, 4,4',4"-tri[phenyl(m-tolyl)amino]triphenylamine, 4,4',4"-tri(carbazole-9-yl)triphenylamine, 1,1-bis[(di-4-tolylamino)phenylcyclohexane, 4,4',4"-tri(diphenylamino)triphenylamine doped with tetrafluoro-tetracyano-quinodimethane, p-doped phthalocyanine, F4-TCNQ doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, hexaazatriphenylene-capronitrile.

9. The light emitting device according to claim 7, characterized in that: The thickness of the anode is 20 to 200 nm; and / or, The thickness of the cathode is 40 to 190 nm; and / or, The thickness of the hole transport layer is 30 to 180 nm; and / or, The thickness of the electron transport layer is 20 to 180 nm; and / or, The light emitting device further comprises a hole injection layer disposed between the anode and the hole transport layer, and the thickness of the hole injection layer is 20-200 nm.

10. A display device, characterized in that: The display device comprises the light emitting device according to any one of claims 1 to 9.